Hard X-ray free-electron laser with femtosecond-scale timing jitter. Issue 11 (November 2017) - Kang, Heung-Sik; Min, Chang-Ki; Heo, Hoon; Kim, Changbum; Yang, Haeryong; Kim, Gyujin; Nam, Inhyuk; Baek, Soung; Choi, Hyo-Jin; Mun, Geonyeong; Park, Byoung; Suh, Young; et al.
Abstract The hard X-ray free-electron laser at the Pohang Accelerator Laboratory (PAL-XFEL) in the Republic of Korea achieved saturation of a 0.144 nm free-electron laser beam on 27 November 2016, making it the third hard X-ray free-electron laser in the world, following the demonstrations of the Linac Coherent Light Source (LCLS) and the SPring-8 Angstrom Compact Free Electron Laser (SACLA). The use of electron-beam-based alignment incorporating undulator radiation spectrum analysis has allowed reliable operation of PAL-XFEL with unprecedented temporal stability and dispersion-free orbits. In particular, a timing jitter of just 20 fs for the free-electron laser photon beam is consistently achieved due to the use of a state-of-the-art design of the electron linear accelerator and electron-beam-based alignment. The low timing jitter of the electron beam makes it possible to observe Bi(111) phonon dynamics without the need for timing-jitter correction, indicating that PAL-XFEL will be an extremely useful tool for hard X-ray time-resolved experiments. The Pohang Accelerator Laboratory X-ray Free Electron Laser (PAL-XFEL) in South Korea has now entered operation with a timing jitter of just 20 fs.